2014
DOI: 10.1590/0100-2945-384/13
|View full text |Cite
|
Sign up to set email alerts
|

Ciclo de produção e demanda térmica de clones da videira 'Concord' sobre diferentes porta-enxertos

Abstract: O objetivo do trabalho foi determinar a duração do ciclo de produção e a necessidade térmica de seis clones de 'Concord' sobre três porta-enxertos no norte do Paraná. Foram avaliados os clones '22', '28', '49', '202', '211' e '225', obtidos pela Embrapa Uva e Vinho, e enxertados sobre os porta-enxertos 'IAC 766', 'IAC 572' e '420-A'. O trabalho foi realizado em área experimental pertencente ao Centro Tecnológico da COROL - Cooperativa Agroindustrial, localizado no município de Rolândia-PR. O experimento foi re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…The degree-day concept assumes the existence of a basis temperature, considered 10°C by other authors (Neis et al, 2010;Borges et al, 2014;Barros et al, 2015), below which vegetal growing can be disregarded (Pezzopane et al, 2008). During the 2014 cycle, these minimum temperatures were below the basis temperature for three days.…”
Section: Resultsmentioning
confidence: 99%
“…The degree-day concept assumes the existence of a basis temperature, considered 10°C by other authors (Neis et al, 2010;Borges et al, 2014;Barros et al, 2015), below which vegetal growing can be disregarded (Pezzopane et al, 2008). During the 2014 cycle, these minimum temperatures were below the basis temperature for three days.…”
Section: Resultsmentioning
confidence: 99%
“…Through a literature search, it was found an influence of IAC 766 and IAC 572 on the phenology of several types of grapevines, but the findings differed from each other. Nonetheless, Borges et al (2014) reported that IAC 572 promotes an extension of the phenological cycle of cv. Concord.…”
Section: Resultsmentioning
confidence: 99%